THE USE OF INTERACTIVE TECHNIQUES IN THE TEACHING OF DISCRETE MATHEMATICS AND MATHEMATICAL LOGIC - Daniel, Jenkins; Kholmatov, Javlon (Science technology&Digital finance, 2023)
This article examines in detail the “work in small groups” method, one of the innovative methods used in the educational process of higher educational institutions. Using the example of a mosaic model on the topic “Checking a system of functions for completeness based on Post’s theorem” of the “Algebras of Reasoning” section of the discipline “Discrete Mathematics and Mathematical Logic”. Ways to organize practical classes using these methods are given. All assigned tasks and answers to them were analyzed.